Radiation Treatment in Women with Ovarian Cancer: Past, Present, and Future - Fields, Emma C.; McGuire, William P.; Lin, Lilie; Temkin, Sarah M. (Frontiers in Oncology, 2017)
Ovarian cancer is the most lethal of the gynecologic cancers, with 5-year survival rates less than 50%. Most women present with advanced stage disease as the pattern of spread is typically with dissemination of malignancy throughout the peritoneal cavity prior to development of any symptoms. Prior to the advent of platinum-based chemotherapy, radiotherapy was used as adjuvant therapy to sterilize micrometastatic disease. The evolution of radiotherapy is detailed in this review, which establishes radiotherapy as an effective therapy for women with micrometastatic disease in the peritoneal cavity after surgery, ovarian clear cell carcinoma (OCCC), focal metastatic disease, and for palliation of advanced disease. However, with older techniques, the toxicity of whole abdominal radiotherapy (WAR) and the advancement of systemic therapies have limited the use of radiotherapy in this disease. With newer radiotherapy techniques, including intensity modulated radiotherapy (IMRT), stereotactic body radiotherapy (SBRT) and low dose hyperfractionation in combination with targeted agents, radiotherapy could be reconsidered as part of the standard management for this deadly disease.